A Simple Allocation Problem - Derman, Cyrus (Management Science, 1959)
The problem studied is that of how to allocate a fixed amount of some resource among various activities where, after a period of time, unused portions of the resource lose their value. Demand for the resource at each station is considered to be random. The problem is a special case of one usually referred to as the distribution of the effort. The question of determining the optimal amount of resource is also discussed.